CLUSTERIZATION OF BALI CATTLE FEED MANAGEMENT AT SIMANTRI IN BADUNG REGENCY - Luzain, Geidha Lailia; Sampurna, I Putu; Nindhia, Tjok Sari (Buletin Veteriner Udayana, 2022)
This study aims to determine the components of feed management that have not been applied intensively in Simantri at Badung Regency and find out that Simantrihas applied feed management intensively. Sampling was done by saturated sampling technique at 50 Simantri. The data obtained were analyzed using hierarchical clusters with dendogram cluster plots with intensive, semi-intensive, and extensive characterizing variables. The results showed feed management components that have not been applied intensively include feeding frequency, feeding time, type of feed given, amount of feed given, and the presence or absence of remaining food. Simantri in Badung Regency which has not implemented intensive feed management as many as 40 Simantri and most of the feed management components have not been applied intensively. The conclusion of this study is that not all Simantri in Badung Regency have applied all components of feed management intensively, and most of Simantri in Badung Regency applied semi-intensive feed management. Suggestions need to be optimized through counseling to achieve a maximum Simantri program.